SOSIALISASI TES KEMAMPUAN DAYA TAHAN CARDIOVASCULAR (VO2MAX) DENGAN MENGGUNAKAN AUDIO BLEEP TEST PADA PERGURUAN PERISAI DIRI SEMEN PADANG - Mardius, Ali; Siswara, Meuthia Rezika; Erianti, Erianti; Astuti, Yuni; Rosmawati, Rosmawati (JURNAL WIDYA LAKSANA, 2020)
This community service activity aims to socialize to trainers and athletes how to measure aerobic capacity and cardiovascular endurance or often called VO2max by using the bleep test. The continuation of this program is that trainers who have been given knowledge about the bleep test can be introduced to other trainers and can practice to their athletes, so that the trainer can know the ability of cardio vascular endurance for each athlete in accordance with the norm VO2Max level, so that achievement can be achieved to the maximum.